Detection of exclusive reactions in the Hermes Recoil Fiber Tracker - Keri, Tibor; Justus Liebig University Giessen (My University, 2008)
The standard model of particle physics describes successfully the fundamental constituents and forces in our world; nevertheless, many details of the subatomic world are still beyond the scope of theoretical predictions. The internal structure of the nucleon has been investigated in detail and it was found that the nucleon spin budget, i.e. the composition of the nucleon spin by the spin and orbital angular momentum of quarks and gluons is not yet understood. It has been measured that the intrinsic quark spin contribution is only about $30%$ of the total spin of the nucleon. A recently developed formalism allows to describe the internal structure of the nucleon by so-called GPDs (Generalized Parton Distributions) in a more complete way than the previously used PDFs (Parton Density Functions). The GPDs are linked by the Ji sum rule to the angular momentum contributions of quarks and gluons. These GPDs can be accessed by the investigation of hard exclusive reactions. DVCS (deeply virtual Compton scattering) is the cleanest exclusive reaction to determine some of these distributions, using lepton beams with different helicity states and charges. HERMES (HERA measurements of spin) is one of the experiments which were carried out to complete the information about the nucleon spin budget. It is located at HERA which is an e-/e+ - p -collider at DESY but uses only the polarized electron- and positron-beam, which is scattered off a gaseous internal target. The HERMES forward spectrometer consists of a set of detectors that are used for tracking, while another set of detectors provides information on particle identification and triggering. In the first phase of HERMES, only forward going particles were detected. Exclusive reactions have been measured using a missing invariant mass technique. In order to improve exclusivity and to enhance the resolution of kinematic variables the HERMES collaboration decided to remove the equipment for the polarized target and to install the RD (Recoil Detector) with an unpolarized target at this position. This detector consists of the Silicon Strip Detector, the SFT (Scintillating Fiber Tracker), the Photon Detector and is surrounded by a 1T superconducting magnet. It provides several space points for tracking and thus momentum reconstruction. The energy deposition in the various detectors is used to achieve particle identification. The main part of the thesis work was the implementation of the SFT and the RD readout system. Before the installation of the RD a series of test runs were carried out to proof the concept of the detector, to measure the internal alignment and to prepare the installation. These test runs for the SFT are described and major results are shown. Furthermore a preliminary analysis of the latest data 06d/06d0 was carried out to show the performance of the installed Recoil Detector in combination with the HERMES forward spectrometer.

Das Standardmodell der Teilchenphysik beschreibt die grundlegenden Bestandteile und Kräfte in unserer Welt. Allerdings gehen viele Aspekte der subatomaren Welt noch über dem Bereich der theoretischen Vorhersagen hinaus. Dazu gehört, daß die Zusammensetzung des Nukleonspins, welches Drehimpuls- und Bahndrehimpulsbeiträge von Quarks und Gluonen enthält, noch nicht vollständig verstanden wird. Der tatsächliche Quarkdrehimpulsbeitrag zum vollständigen Nukleonspins beträgt nur etwa 30%.Ein neuentwickelter Formalismus ermöglicht die interne Struktur des Nukleons durch so genannte GPDs (Generalized Parton Distributions) auf eine umfangreichere Art als die vorher verwendeten PDFs (Parton Density Functions) zu beschreiben. Diese GPDs werden durch die Summenregel von Ji mit den Beiträgen des Gesamtdrehimpulses von Quarks und Gluonen verknüpft und können durch die Untersuchung von harten exklusiven Reaktionen bestimmt werden. DVCS (deeply virtual Compton scattering) ist die einfachste exklusive Reaktion, um unter Verwendung von Leptonenstrahlen mit verschiedenen Helizitäten und Ladungen einige dieser Verteilungen zu messen. HERMES (HERA measurements of spin) ist eines der Experimente zur Untersuchung des Nukleonenspins. Es befindet sich innerhalb HERA (Hadronen-Elektronen Ring Anlage), welches ein e-/e+ - p - Beschleuniger am DESY (Deutsches Elektronen-Synchrotron) ist. Bei dem HERMES Experiment wird nur der polarisierte Elektron-/Positron-Strahl verwendet, welcher an wahlweise polarisierten oder unpolarisierten Gasen gestreut wird. Das Vorwärtsspektrometer vom HERMES Experiment besteht aus Spurdetektoren sowie Detektoren zur Teilchenidentifikation. In der ersten Phase der Datennahme wurden nur die Teilchen in Vorwärtsrichtung detektiert. Die Kinematik von exklusiven Reaktionen wurden unter der Verwendung fehlender invarianter Restmasse vervollständigt. Um die Exklusivität zu verbessern und um die Auflösung kinematischer Variablen zu erhöhen, wurde das HERMES Vorwärtsspektrometer um den RD (Recoil Detector) erweitert, wobei danach die Messungen mit unpolarisierten Gasen erfolgten. Dieser Detektor besteht aus dem Silicon Strip Detector, dem SFT (Scintillating Fiber Tracker), dem Photon Detector und wird von einem supraleitenden Magneten mit einer Feldstärke von 1T umgeben. Er stellt mehrere Raumpunkte für Spurrekonstruktion und damit für die Impulsrekonstruktion zur Verfügung. Die Energieverluste der Teilchen beim Passieren der verschiedenen Detektoren werden verwendet, um die Teilchen identifizieren zu können. Der Hauptteil dieser Arbeit war die Implementierung des SFT- und des RD-Auslesesystems. Vor der Installation des RD wurde eine Reihe von Messungen mit verschiedenen Versuchsaufbauten durchgeführt, um das Konzept des Detektors zu prüfen, die interne Ausrichtung zu messen und die Installation vorzubereiten. Diese Messungen für den SFT werden beschrieben und die wesentlichen Resultate werden gezeigt. Ausserdem wurde eine erste Analyse der aktuellsten Datenproduktion 06d/06d0 durchgeführt, um die Leistung des installierten RD in Verbindung mit dem HERMES Vorwärtsspektrometer zu zeigen.
Nachweis von exklusiven Reaktionen in dem Hermes Recoil Fiber Tracker
Keywords: GPD; DIS; DVCS; Asymmetrie; Spektrometer; GPD; DIS; DVCS; Asymmetry; Spectrometer; ddc:530